Pengaruh Ekspor, Impor, Inflasi dan Pengangguran Terhadap PDB Per Kapita di Negara G20 - Aliah Afifah; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the effect of exports, imports, inflation, and unemployment on GDP per capita in G20 countries. The type of data used in this study is secondary data using panel data which is a combination of 2020-2024 time series data and cross-section data of 20 G20 member countries. The research was obtained from publications of the World Bank and other related agencies. The analysis used was descriptive analysis and inductive analysis. For the inductive analysis, this study employed panel data regression with a fixed effects model. The results showed that exports have a positive and significant effect on GDP per capita in G20 countries. The export variable has a positive and significant effect on GDP per capita in G20 countries. Furthermore, the import variable has a negative and significant effect on GDP per capita in G20 countries. The inflation variable has a positive but insignificant effect on GDP per capita in G20 countries. This study also found that the unemployment variable has a negative and significant effect on GDP per capita in G20 countries. Keywords: Exports, Imports, Inflation, Unemployment, GDP Per Capita